Purification and characterization of endoglucanase from Dictyoglomus - Kwek, Yan Wei, 1993- , author; Goh Kian Mau, supervisor 325080; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Biologi - Industri)) - Universiti Teknologi Malaysia, 2017